(3GdJYdje GdKGfhj GdQSej (B: (3hGbYg hTQhW JWhjQgs - (3GdeDJeQ GdJQHhj (B5 2006 (3HjQhJs ((3HjQhJs (3QGHWI CSGJPI GdJYdje GdKGfhj aj dHfGfs, 2007)
(3jJfGhd gPG GdcJGH GYeGd GdeDJeQ GdJQHhj GdNGeS GdPj YbO aj (B26-27(3CjGQ (B2006 (3aj HjQhJ(B. (3JVef GdeDJeQ (B5 (3fOhGI fGbTJ GdehGVjY GdJGdjI(B: - (3GdJYdje GdKGfhj GdQSej(B: (3GdHYO GdhWfj hGdSjGSI GdJQHhjI GdQSejI(B. - (3GdKGfhjI GdQSejI(B: (3GdJfXje GdOGNdj hGdYdGbI eY GdeMjW(B. -(3QGHWI CSGJPI GdJYdje GdKGfhj(B: (3GdOhQ GdfbGHj hGdJQHhj(B. - (3CSGJPI GdJYdje GdKGfhj GdQSej(B: (3GdEYOGO hGdJOQjH hGdJWhjQ Gdegfj(B. - (3WdHI GdKGfhjI GdQSejI(B: (3eYWjGJ hfGFL(B.s
(3GdfhY (B: (3cJGHs
Keywords: (3GdGSJTQGas; Educational prospective; Prospective; Public Sector Secondary Education; Secteur Public Cycle Secondaire; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs